Effects of plyometric and directional training on physical fitness parameters in youth soccer players - Michailidis, Y.; Tabouris, A.; Metaxas, T. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate whether the combination of a soccer training session, plyometric training, and change-of-direction (COD) exercises would enhance soccer ability to a greater extent than training on its own in youth soccer players. Methods: Thirty-one youth players participated in this study (age: 12 [0.8] y). Players were randomly separated into 2 groups: a control group (CG, n = 14) and an intervention group that performed extra plyometric training and COD exercises (intervention group, n = 17). The duration of the training program was 6 wk. Players' performances in sprint (10 and 30 m), countermovement jump, squat jump, long jump, multiple 5-bound, T-test, and Yo-Yo Intermittent Endurance Test 1 were measured before and after the training program. Results: Players' performance in acceleration, T-test, and long jump improved in both groups (P = .03, P = .002, and P = .001, respectively). Squat-jump performance increased in the intervention group (15.2%, P = .003) and slightly decreased in the control group (P = .003). The performances of the 2 groups differed significantly in squat jump and long jump (P = .003 and P = .038, respectively). Conclusions: This study indicates that a short-term combined program of plyometric training and COD exercises can improve jumping ability, acceleration, and endurance parameters in youth soccer players. The small training effect could be explained when taking into account the level of the participants, the duration of the program, and the low volume of COD exercises used.